Amlodipine drug therapeutic failure: a rare case report - Thakkar, Kandarp K.; Shah, Kartik; Rana, Devang; Malhotra, Supriya D.; Patel, Pankaj R. (International Journal of Basic & Clinical Pharmacology, 2017)
Drug Therapeutic failure is a rare condition which is underreported in recent scenario. It is important for the chronic diseases like Hypertension where it could lead to fatal outcome. In our case report elderly male patient taking tablet Amlodipine once daily as antihypertensive medication and had 2 years without any events. Patient came to the emergency department with the complaint of altered sensorium and elevated blood pressure. The mechanism for sudden increase in blood pressure (Decreased Therapeutic Response) in patient with ongoing treatment with amlodipine could be due to sympathetic over activity (e.g. stress), pharmacokinetic variation or counterfeit drug.